Effect of stress on the leaf anatomy of sugarcane cultivars with different drought tolerance (Saccharum officinarum, Poaceae) - Taratima, Worasitikulya (2020)
ABSTRACT. Introduction: Drought is an important stress factor for sugarcane production in many areas of the world. Water proportion and moisture indices are applicable information for agronomic planning to forecast water excess or deficit during the crop cycle. Objective: Leaf anatomical features of two different sugarcane Saccharum ‘UT12’ (drought susceptible cultivar) and Saccharum ‘UT13’ (drought tolerant cultivar) were compared under early drought stress situation between 30 and 90 days after planting. Methods: Forty leaf anatomical features were investigated using peeling and free hand sectioning technique. Results: Some anatomical characteristics showed response to drought stress. Saccharum ‘UT12’ demonstrated higher sensitivity toward anatomical characteristics than Saccharum ‘UT13’. A total of 23 and 15 out of the 40 anatomical characteristics showed significance in Saccharum ‘UT12’ and Saccharum ‘UT13’, respectively. Some anatomical features such as cell wall and cuticle thickness, vascular bundle size, stomatal size and density can be used as important markers for drought stress assessment in sugarcane leaf. Conclusions: This is the first report describing comparative leaf anatomy of sugarcane Saccharum ‘UT12’ and Saccharum ‘UT13’ in Thailand under drought stress. Results will provide important information to improve adaptation mechanisms of tolerant sugarcane cultivars under initial drought stress situations.